Understanding mechanisms of change in psychotherapies for personality disorders - Kramer, Ueli; McMain, Shelley; Levy, Kenneth N. (Kenneth Neil) 1963- (American Psychological Association, 2024)
This book presents a holistic approach to treating patients with personality disorders that seeks to inspire psychotherapists and encourage innovation. Focusing on core mechanisms of change that span different therapeutic approaches, this book invites clinicians and researchers to join a dialogue with the authors, as they examine personality disorders from different theoretical perspectives, including dialectical behavior therapy, transference-focused therapy, plan analysis, clarification-oriented, and emotion-focused therapies. The authors explore five functional domains that underlie assessment and treatment for personality disorders: emotion dysregulation, disturbed social interaction, identity problems, impulsivity, and cognitive disturbances. Each domain is analyzed through an in-depth case example, with case conceptualizations and the careful evaluation of clinical decisions that must be made at key points in therapy. The authors then compare their different approaches, emphasizing commonalities among them while also pointing out notable differences. They also offer clear and compelling recommendations for maintaining and strengthening the therapeutic alliance. The final chapter synthesizes key takeaways from across the book to create a clear path towards enhancing clinical practice"-- Provided by publisher.